Regulating the micromixing efficiency of a novel helical tube reactor by premixing behavior optimization. Issue 7 (30th January 2017) - Luo, Jiang‐Zhou; Chu, Guang‐Wen; Luo, Yong; Arowo, Moses; Sun, Bao‐Chang; Chen, Jian‐Feng
Abstract : In this work, a novel helical tube reactor (HTR) was constructed, including a pre‐mixer for adjusting the premixing behavior of reactants and a helical tube as a further mixing unit. The pre‐mixer was modified to optimize the premixing behavior by using two methods, named as tangential‐feeding and insertion of a helical baffle. The premixing behaviors were investigated via computational fluid dynamics (CFD) simulation. Simulation results indicated that both methods can change the fluid flow, enhance the turbulence kinetic energy, and improve the premixing performance in the pre‐mixers. Based on the results of CFD simulation, it could be predicted that the micromixing efficiency of the HTR can be regulated by these methods accordingly. Then the predicated results were confirmed experimentally by a parallel competing reaction. Furthermore, the relationship between the premixing performance increasing and the corresponding micromixing efficiency increasing of the HTR was quantitatively analyzed. © 2017 American Institute of Chemical Engineers AIChE J, 63: 2876–2887, 2017